Fit for purpose? the strengths and weaknesses of Gauteng maternity services health care organisation / configuration in the context of reducing maternal deaths - Chauke, Hlengani Lawrence (University of the Free State, 2021)
BACKGROUND: Despite the availability of evidence-based and cost-effective interventions that are accessible to low and middle-income countries (LMICs), women continue to die of preventable pregnancy-related causes worldwide. Sub-Saharan Africa (SSA) carries a disproportionate burden of maternal mortality (68% of the global burden) relative to its size (has just below 16% of the world’s total population). The high burden of maternal deaths in SSA, including other LMICs, has been attributed to the failure of its healthcare system, in particular, poor quality of primary healthcare (PHC) orientated district healthcare services (DHS). The DHS-PHC model is the statutory model for service delivery in South Africa. This model has been blamed in studies conducted in low-and middle-income countries (LMICs) for the poor quality of both maternal and general healthcare services. Consequently, calls for the centralisation of maternity services to hospitals have started to emerge, the argument in favour of such a move is that centralising maternity services to hospitals would improve pregnant women’s access to emergency maternity healthcare services and skilled attendants in a timely manner. Others have however argued that a hospital-based model of maternity care is both costly and unsustainable for countries with limited resources and instead this group have called for the strengthening of the DHS-PHC. Informed by contextual realities, various African countries, as well as provinces in South Africa implemented different strategies aimed at strengthening the DHS-PHC model. For example, in the Western Cape and Gauteng, this took the form of a Comprehensive Service Plan (CSP) and Cluster Policy Framework (CPF). The two healthcare frameworks are based on a regional model but differ in philosophy and governance structures. Both models aim to strengthen the district health care system, improve health service efficiency as well as quality of care. Although only signed into policy in January 2019, the CPF model has been in operation in the Charlotte Maxeke Johannesburg Academic Hospital Cluster (CMJAH) since 2016, mainly in the Obstetrics and Gynaecology and Surgical disciplines. Unlike the Western Cape’s CSP model, the Gauteng CPF healthcare model has not been subjected to scientific evaluation since its implementation. Because maternal and neonatal healthcare services are national and provincial priority areas, maternity healthcare services presented a unique opportunity to evaluate the CPF, a healthcare innovation aimed at improving the quality and governance of healthcare services. AIM: The aim of the study was to assess the strengths and weaknesses of the organization/ configuration of maternity healthcare services in Gauteng, in particular, the CPF as implemented in the CMJAH maternity cluster in order to identify gaps/healthcare barriers and use this information to recommend healthcare services improvement strategies. METHODOLOGY: Informed by Stufflebeam’s Context, Input, Process and Product (CIPP) theoretical model /framework, and a convergent mixed method research design, quantitative and qualitative data were simultaneously and independently collected, analysed, results synthesized and merged through a process of triangulation. The quantitative component involved an audit of maternity healthcare facilities in terms of resources (number of facilities, distribution, bed capacity, human resource), service load (deliveries) and maternal deaths. Semi-structured interviews with frontline healthcare workers and their immediate supervisors/managers, facility visits and the review of the cluster morbidity and mortality (M&M) meetings minutes, as well as the Cluster Policy Framework (CPF), constituted the qualitative component. RESULTS: The CPF managed to establish clinical governance, standardised protocol, improved coordination of healthcare services, including creating an enabling environment for support, collaboration and sharing of knowledge and skills among healthcare workers from different levels of care and healthcare. During the period under study, the cluster saw a modest and sustained decline in maternal mortality despite an increase in maternity deliveries. However, the CPF faced challenges in the form of a mismatch between the demand and supply side of healthcare services. The mismatch was due to a number of factors, among those, poor leadership, management, governance, infective implementation of the CPF and a high rate of provincial and international migration. Together with leadership and management challenges, the mismatch between the demand and supply side of healthcare services, resulted in the over burdening of maternity healthcare services, increase in patient adverse events, disgruntled healthcare workers, poor quality of care and an increase in medico-legal challenges thereby setting on the stage, a vicious cycle with no end point. CONCLUSION: Gauteng CPF is an excellent example of health system innovation with a potential to strengthen the quality and coordination of not only maternity but healthcare services in general. The model retains all the advantages of the DHS-PHC model and at the same time, focus on improving clinical governance, distribution and sharing of scare resources. Poor leadership, governance, management lack of effective policy implementation, inadequate infrastructure, shortage and ineffective management of human resources, among other factors, have created bottlenecks and challenges in the health system, limiting the CPF model’s potential. These challenges would need to be addressed in order for the CPF to deliver on its promise. Failure to do so could result in a catastrophic failure of the much-awaited NHI.
Thesis (Ph.D. (Obstetrics and Gynecology))--University of the Free State, 2021
Keywords: Cluster; Configuration; District; Deaths; Healthcare; Maternal; Maternity; Primary; Organization; Services